Caracterización de los planes de estudio a nivel de pregrado de las facultades de Odontología de universidades privadas en Colombia (2022)
The objective of this study was to characterize the dentistry curricula of private universities in Colombia. Materials and methods: a cross-sectional descriptive study was carried out, with an intentional sample of 16 private universities in Colombia. Study and analysis variables were established, such as program content, number of academic credits, number of subjects, duration, skills acquired by the student, high-quality accreditation, and lines of research